Komunistyczna Partia Zachodniej Ukrainy i tzw. proces łucki - Bojko, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
Communist Party of Poland KPP, operating within the territory of the Second Polish Republic, displayed strong racially-motivated separatist tendencies, which lead to the creation of the Communist Party of Western Ukraine KPZU — an autonomous movement operating within the KPP structures. In the mid-thirties of 20th century KPZU activists were put in the dock in the so-called Luck trial, the most prominent trial of communists in pre-war Poland. Drawing mainly upon court records, the author presents the history of this marginal political party and describes the Luck trial.
Keywords: Komunistyczna Partia Zachodniej Ukrainy; proces łucki; Komunistyczna Partia Polski; komuniści w II Rzeczypospolitej